2017
DOI: 10.1016/j.bjane.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Inadvertent injection of succinylcholine as an epidural test dose

Abstract: Background and objectives: Epidural action of neuromuscular blocking agents could be explained under the light of their physicochemical characteristics and epidural space properties. In the literature there are few cases of accidental neuromuscular agent's epidural administration, manifesting mainly with neuromuscular blockade institution or fasciculations. Case report: We report a case of accidental succinylcholine administration as an epidural test dose, in a female patient undergoing scheduled laparotomy, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…They reported shortness of breath, dysarthria, and fasciculations in the thoracic part of the trunk, upper extremities, and face two minutes after accidental epidural administration of 100 mg of succinylcholine, which was managed with the induction of general anaesthesia. Pourzitaki et al reported the administration of 125 mg of Sux during combined spinal and epidural anesthesia without any neurological or cardiovascular complications during the postoperative period [ 7 ]. They reported that diazepam taken orally can lessen the adverse effects of accidental epidural administration of Sux.…”
Section: Discussionmentioning
confidence: 99%
“…They reported shortness of breath, dysarthria, and fasciculations in the thoracic part of the trunk, upper extremities, and face two minutes after accidental epidural administration of 100 mg of succinylcholine, which was managed with the induction of general anaesthesia. Pourzitaki et al reported the administration of 125 mg of Sux during combined spinal and epidural anesthesia without any neurological or cardiovascular complications during the postoperative period [ 7 ]. They reported that diazepam taken orally can lessen the adverse effects of accidental epidural administration of Sux.…”
Section: Discussionmentioning
confidence: 99%